Effect of trans-fat free shortening and temperature on the rheological characteristics of pie crust dough and quality of pie crust - Leelawat, Bootsrapa; Mundee, Pajaree (Food and Applied Bioscience Journal, 2017)
This research purpose was to evaluate the effect of Trans-fat free shortening and temperature on the rheological characteristics of pie crust dough and quality of pie crust. Lubricated squeezing flow techniques were used to evaluate the rheological characteristics of pie crust dough prepared from Trans-fat free shortening and commercial shortening. The relationship between biaxial extensional viscosity and biaxial extensional strain rate of both shortenings can be described by a power-law model with a biaxial consistency coefficient (KB) of 14.63 3.07 and 8.13 2.07 kPa.s as well as a flow behavior index (n) of 0.31 0.09 and 0.32 0.07, respectively. The pie crust dough from each shortening prepared at 5 temperature levels (5, 10, 15, 20 and 25°C) showed all extensional thinning behaviors. The biaxial consistency coefficient of pie crust dough from commercial shortening at every temperature level showed significantly higher than the one from Trans-fat free shortening. However the flow behavior index of pie crust dough from commercial shortening prepared at 25°C (0.34 0.10) was not significantly different from Trans-fat free shortening prepared at 10 and 15oC. The hardness and fracturability of pie crust was then evaluated by Texture Analyzer and found that the hardness of pie crust from commercial shortening was greater than from Trans-fat free shortening for each temperature from 5-25°C. Nevertheless the fracturability of pie crust with commercial shortening at 5-25 °C was not significantly different from the pie crust with Trans-fat free shortening at 10, 15 and 20 °C.